2020
DOI: 10.31896/k.24.2
|View full text |Cite
|
Sign up to set email alerts
|

Steiner's Hat: a Constant-Area Deltoid Associated with the Ellipse

Abstract: The Negative Pedal Curve (NPC) of the Ellipse with respect to a boundary point M is a 3-cusp closed-curve which is the affine image of the Steiner Deltoid. Over all M the family has invariant area and displays an array of interesting properties.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…One open question is whether a common thread exists which links the Steiner Hat [4], the Hybrid, and Pseudo-Talbot curves, since all of them are area-invariant over M on the ellipse. Furthermore, if a continuous family of curves exists with this area-invariance property.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One open question is whether a common thread exists which links the Steiner Hat [4], the Hybrid, and Pseudo-Talbot curves, since all of them are area-invariant over M on the ellipse. Furthermore, if a continuous family of curves exists with this area-invariance property.…”
Section: Discussionmentioning
confidence: 99%
“…Three cases are shown, for M (i) interior (top left), (ii) on the boundary (top right), and (iii) at the center (bottom) of the ellipse. For case (ii) the area of the curve is invariant for all M[4]. Case (iii) yields Talbot's Curve[11] (in general it does not pass through the foci, but for the case shown, a/b = 2, it does).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Also shown are envelopes (pink) to the ellipse families. For X3 (top right), the envelope is a half-sized Steiner's hat [9]; for X2 (bottom left) the envelope is an ellipse of fixed axes, internally tangent to E at one point. Interestingl, all envelopes are area-invariant wrt V1.…”
Section: Locus Center Translationmentioning
confidence: 99%
“…More recently, with the help of a computer algebra system (CAS), we showed that 29 out of the first 100 entries in [11] are ellipses over billiard 3-periodics, though what determines ellipticity is still not understood [8]. We've also studied properties (e.g., area invariance) of the negative pedal curve (NPC) of the ellipse with respect to a point on its boundary [9] as well as its pedal-like [11] which are both on the Euler line and which are fixed linear combinations of X2 and X4.…”
Section: Introductionmentioning
confidence: 99%